Posted by **bryan** on Wednesday, March 7, 2012 at 11:46am.

Let z = ∫e^(sin(t))dt from x to y

a = x

b = y

I tried thinking about it like a chain rule but even then i'm a little unsure.

I know dz/dt = e^(sin(t)). Can you please point me in the right direction if i'm supposed to use the chain rule.

## Answer This Question

## Related Questions

- calculus - Let z = ∫e^(sin(t))dt from x to y a = x b = y I tried thinking ...
- calculus - Let z = ∫(e^sin(t)dt) from x to y a = x b = y I tried thinking ...
- calculus - Find dz/dy and dz/dx Let z = ∫e^(sin(t))dt from x to y a = x b...
- Calculus - Evaluate ∫ (cos(x))^(1/2)sin(x)dx Let u = cos(x)? ∫ (u)^(...
- Calculus - Use a Riemann sum with n = 3 terms and the right endpoint rule to ...
- calculus II - ∫ tan^2 x sec^3 x dx If the power of the secant n is odd, ...
- Calculus - Integrate 1/sinx dx using the identity sinx=2(sin(x/2)cos(x/2)). I ...
- Math integrals - What is the indefinite integral of ∫ [sin (π/x)]/ x^...
- Calculus - Alright, I want to see if I understand the language of these two ...
- Calculus - Hello, I just wanted to verify if my work was good. Calculate the ...

More Related Questions